The effects of rbST (POSILAC®) on heat stressed, lactating, dairy cows - John F. Smith; John E. Shirley; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1997)
Two hundred cows located on a commercial dairy in Mesquite, NM were used to evaluate response to rbST (POSILAC®) during heat stress in the summer of 1996. Cows were paired by days in milk (average = 153 d at initiation of experiment), parity, and milk yield (average = 92 lb at start of experiment). Prior to initiation of the experiment, all cows received rbST, then rbST treatment was discontinued for one cow from each pair. Milk production was monitored for 4 months. No interactions were detected between lactation number and treatment. Cows maintained on rbST gained .09 of a score (1 to 5scale) less (P<.05) body condition but produced more (P<.05) milk in June, July, August, and September. The average milk productions for rbST-maintained vs rbST-discontinued cows were 80.7 vs 73.5 lb/d in June, 80.1 vs 74.6 lb/d in July, 72.6 vs 67.1 lb/d in August, and 65.1 vs 59.2 lb/d in September. Although rbST-discontinued cows had greater declines in production discontinued cows had greater declines in production persistency was similar between groups during the final 3 months. Under conditions of heat stress, cows maintained on rbST produced 6.2 lb/d more milk than cows for which treatment with rbST was discontinued.; Dairy Day, 1997, Kansas State University, Manhattan, KS, 1997;
Keywords: Dairy Day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-100-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 792; Dairy; rbST; Heat stress; Lactating cows